Maria Bonita: a linalool type basil cultivar - Blank, Arie Fitzgerald; Souza, Evanildes Menezes de; Blank, Maria de Fátima Arrigoni; Paula, José Welton Azevedo de; Alves, Péricles Barreto (Pesquisa Agropecuaria Brasileira, 2007)
'Maria Bonita' is derived from the accession PI 197442, from the Germplasm Bank North Central Regional PI Station, USA. It is a basil cultivar with a rounded canopy, rose petals and purple sepals, and it is indicated for Brazilian Northeast region. 'Maria Bonita' presents erect growth habit, which is an advantage for both manual and mechanized harvest. The average yield of leaves dry weight and inflorescences was 20.97 g per plant, 26.34% higher than the control 'Genovese'. It presents 4.96% essential oil content, and yield of 1.18 mL per plant. The major chemical constituent is linalool (78.12%). Its essential oil presents antinociceptive and antigiardial activities.